Art of happiness: handbook for living - Dalai Lama (London, 1999)
In this unique and important book, one of the world's great spiritual leaders offers his practical wisdom and advice on how we can overcome everyday human problem and achieve lasting happiness. The Art of Happiness is a highly accessible guide for a western audience, combining the Dalai Lama's eastern spiritual tradition with Dr Howard C. Cutler's western perspective. Covering all key areas of human experience, they apply the principles of Tibetan Buddhism to everyday problems and reveal how one can find balance and complete mental and spiritual freedom.
Keywords: Happiness